中學生歷史思維能力之探究：歷史觀點取替模式的應用 Historical Thinking Development of Students: Applying the Historical Perspective-Taking Model - 楊淑晴 Shu-Ching Yang; 黃麗蓉 Li-Jung Huang (National Taiwan Normal University, 2011)
近來歷史教育的目標，已逐漸從傳統史實傳遞中鬆綁，走向強化學生歷史思維能力之趨勢。其中，「歷史神入」（historical empathy）與「歷史觀點取替」（historical perspective taking,HPT）乃為一適合應用於中學生歷史思維教學的切入點。本研究參照Hartmann 與Hasselhorn（2008）提出的歷史觀點取替模式為架構，編擬一份適用於國、高中生之歷史觀點取替測驗工具，以高雄市某八年級、九年級學生，以及某高中二年級學生為施測對象，得有效問卷1,017份。研究結果顯示，因素分析抽取出含括「以現代觀點取替」（present-oriented perspective taking, POP）和「歷史人物的角色」（the role of the historical agent, ROA）的「現代觀點」與「歷史脈絡的理解能力」（students' ability for historical contextualization, CONT）兩個因素。年級、性別之差異結果發現：男、女生在整體歷史思維能力上並無顯著差異存在；但在「歷史人物的角色」層面中，女學生的分數比男學生高；在「歷史脈絡的理解能力」因子中，九年級學生的得分顯著高於八年級學生，而高二學生的得分亦顯著高於八年級學生。相關分析研究結果則顯示中學生閱讀歷史小說或故事的頻率愈高，愈會將歷史相關事件放在合適的脈絡中去理解、思考。本研究並進一步針對研究結果提出具體建議，供教師、後續研究者作為參考與修訂之方向。 History education should emphasize student competencies of historical thinking instead of learning historical facts. Of all the competencies, historical empathy and historical perspectivetaking are well adopted points for teaching historical thinking to high school students. This study uses the historical perspective-taking (HPT) model (Hartmann & Hasselhorn, 2008) to develop an HPT measure, to investigate the historical perspective-taking of high school students. In total, 1,017 participants were recruited from the 8th, 9th and 11th grade students within the Kaohsiung County. The factor analysis results show that the two factors of present perspective and student ability for historical contextualization (CONT) with good reliability. The factor of the present perspective includes present-oriented perspective taking (POP) and the role of the historical agent (ROA). The findings revealed no gender differences on the entire HPT measure, but girls scored higher on ROA than boys. For CONT, second-grade senior high school students outperformed the second-grade junior high school students, and the third-grade junior high school outperformed the second grade. Based on the findings, this study proposes suggestions for history teachers and future studies.